As mudanças da educação do RN nos idos de 1950 e 1960 :a prática de Lia Campos - Vieira, Daniela Fonseca (2005)
The present study investigates and analyzes the participation of the teacher Lia Campos, during the 50 s and 60 s years, in the norte-riograndense educational organization. The choice of the period is justified because was at this the time what this teacher remained in the potiguar lands, working in favor of the education. In the search of data that informed me concerning her actions, I cover quantities as the Public Archive of the Great River of the North, Historical Institute and Geographic of the Rio Grande do Norte and the Center of Supplementary Studies Teacher Lia Campos, in the task to obtain photographs and verbal stories of friends and fellow workers, periodicals of the time, laws and decrees. Based on the primary education, the work of Lia Campos shows the relevance of the teaching formation for this level of education and the way as the ones that in it work can lead their conceptions and daily practical tasks. This way, I evidence that the cited teacher promotes, in this State, a series of activities as: survey and systematization of the school net; organization of the administrative stuff of the schools; qualifications and courses of improving for lay professors, as well as implantation of the Law of the Education nº 2.171/1957. Through this analysis I show as this teacher left printed her mark in the Rio Grande do Norte historiography by means of her actions, being therefore remembered for that they had followed her experience in norte-riograndense lands